Culture and Differentiation of Human Adipose Tissue Mesenchymal Stromal Cells within Carriers Based on Sea Sponge Chitin Skeletons - Rogulska, Olena Y.; Mutsenko, Vitaliy V.; Revenko, Elena B.; Petrenko, Yuriy A.; Ehrlich, Hermann; Petrenko, Aleksandr Y. (Problems of Cryobiology and Cryomedicine, 2013)
N/AProbl Cryobiol Cryomed 2013; 23(3):267–270.